2014
DOI: 10.1371/journal.pone.0106189
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Impairs Reconsolidation of Fear Memories in a Rat Model of Post-Traumatic Stress Disorder (PTSD)

Abstract: Xenon (Xe) is a noble gas that has been developed for use in people as an inhalational anesthestic and a diagnostic imaging agent. Xe inhibits glutamatergic N-methyl-D-aspartate (NMDA) receptors involved in learning and memory and can affect synaptic plasticity in the amygdala and hippocampus, two brain areas known to play a role in fear conditioning models of post-traumatic stress disorder (PTSD). Because glutamate receptors also have been shown to play a role in fear memory reconsolidation – a state in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 59 publications
(71 reference statements)
0
16
1
1
Order By: Relevance
“…Experiments were performed from 1000h to 1600h. The sample sizes were determined in concordance with our previous work using the conditioned-freezing behavioral assay (Meloni et al, 2014)and c-Fos analyses (Meloni and Davis, 2000). All animal procedures were approved by McLean Hospital’s Institutional Animal Care and Use Committee (Office of Laboratory Animal Welfare Assurance number A3685-01) in accordance with the National Institute of Health Guide for the Care and Use of Laboratory Animals (8 th Edition) .…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Experiments were performed from 1000h to 1600h. The sample sizes were determined in concordance with our previous work using the conditioned-freezing behavioral assay (Meloni et al, 2014)and c-Fos analyses (Meloni and Davis, 2000). All animal procedures were approved by McLean Hospital’s Institutional Animal Care and Use Committee (Office of Laboratory Animal Welfare Assurance number A3685-01) in accordance with the National Institute of Health Guide for the Care and Use of Laboratory Animals (8 th Edition) .…”
Section: Methodsmentioning
confidence: 92%
“…Rats were trained and tested for fear conditioning using procedures adapted from Phillips and LeDoux (1992) as described (Meloni et al, 2014). These procedures enabled us to evaluate the expression of conditioned freezing to both context alone and cues (a tone presented within the same context) that were conditioned while brain PACAP levels were elevated.…”
Section: Methodsmentioning
confidence: 99%
“…Some behavioral therapies have been explicitly designed to leverage the reconsolidation process. 36 Other studies have sought to combine therapy with pharmacologic agents that may help to block the reconsolidation of traumatic memories (eg, propranolol 37 or xenon gas, the latter of which is thought to inhibit the N -methyl- d -aspartate receptor 38 ). A recent study also demonstrated the possibility of using the globally amnestic properties of electroconvulsive therapy to disrupt the reconsolidation of memories.…”
Section: Theme 3: Memory Reconsolidationmentioning
confidence: 99%
“…[38] Indeed, Xe’s general biomedical applications are well-documented: it is a functional anesthetic; [39] recently, it has also been implicated as a possible performance-enhancing drug as well as a potential treatment for PTSD patients. [40] Importantly here, 129 Xe also possesses an extraordinarily sensitive chemical shift—causing its resonance frequency to vary over 200 ppm simply from being physically associated with different chemical environments—enabling HP 129 Xe to be a sensitive “spin-spy” of its local surroundings. HP 129 Xe can also be a source of hyperpolarization for other systems using various polarization-transfer techniques, [41] although such approaches to date have not commonly been exploited for biomedical applications.…”
Section: Spin-exchange Optical Pumping (Seop)mentioning
confidence: 99%